New Observation in Biocontrol of Penicillium caperatum against Fusarium oxysporum on Saposhnikovia divaricata and as a Plant Growth Promoter - Zhongming Han; Jiao Wang; Yanzhe Ding; Zhuo Sun; Yan Wang; Yuyi Wang; Limin Yang; Yunhe Wang (Fermentation, 2023)
Fusarium oxysporum, a common fungal pathogen that infects economic crops, causes Fusarium wilt disease to Saposhnikovia divaricata at an annual incidence rate of more than 15%. This study aimed to assess the potential of rhizospheric fungi as antifungal agents against Fusarium wilt of Saposhnikovia divaricata. In this study, 104 fungi were isolated from S. divaricata rhizospheric soil. Twelve rhizospheric strains that showed antagonistic activity against F. oxysporum, MR-16, MR-32, MR-38, etc., were screened out. Biocontrol activities of the twelve strains, especially MR-16, were subsequently characterized and evaluated. Strain MR-16 as potential stock for biocontrol had good antibiotic activity against F. oxysporum in vitro experiment. Based on the analysis of morphological properties and rDNA internal transcribed spacers (ITS), we identified an isolate MR-16 as Penicillium caperatum (GenBank No. OK287146.1), a new record of this species of China. The results of the in vitro antagonistic assay indicated that the conidial germination rate was significantly decreased, and the mycelia morphology of F. oxysporum induced change via the culture filtrate of P. caperatum MR-16, such as deformation and degradation. In an outdoor pot experiment, inoculation of S. divaricata plants with F. oxysporum created severe wilting symptoms; however, in inoculation trials, MR-16 effectively suppressed disease lesions, with a strong control efficacy of 60.76%. In addition, strain MR-16 could successfully colonize and form stable populations in the soil, and it showed a continuous positive growth-promoting effect on S. divaricata plants.